Surgical Treatment of Radial Nerve Injuries Associated With Humeral Shaft Fracture—A Single Center Experience - Rasulić, Lukas; Djurašković, Slavko; Lakićević, Novak; Lepić, Milan; Savić, Andrija; Grujić, Jovan; Mićić, Aleksa; Radojević, Stefan; Puzović, Vladimir; Maletić, Miloš; Mandić-Rajčević, Stefan (Frontiers in Surgery, 2021)
Radial nerve injuries are often associated with humeral shaft fractures. The results of treatment of these injuries, by contemporary surgical approaches, remain diverse. In this paper we presented the outcomes and analyzed the patient, clinical, and surgical procedure related characteristics and factors that may influence the outcome overall, in 77 patients treated at Clinic for neurosurgery, Clinical Center of Serbia during a 20 years period. The nerve injuries were verified by US and EMNG. The majority of patients were treated by neurolysis or sural nerve grafting, while only few were treated by direct suture. The final recovery was evaluated by muscle strength assessment and classified using MRC. We analyzed extension of the wrist, extension of the fingers including the thumb, and abduction of the thumb. All statistical procedures were performed using IBM SPSS v26.0. The patients that had been treated by direct suture were excluded from the statistical analysis. There was a significant statistical difference in MRC grade following the treatment. The total rate of useful functional recovery was achieved in 68 (88.31%) out of all studied patients, out of whom 20 (29.41%) achieved excellent recovery, 26 (38.23%) achieved good recovery and 23 (33.82%) achieved fair recovery. Only 8 (10.39%) out of all studied patients achieved poor recovery. The injured nerves, that were preserved in continuity, acquired by a low-energy trauma, and treated earlier than the 6 months were associated with better functional outcome following the surgery. In addition, there was a trend of better functional improvement with aging. The expectant management followed by surgery of radial nerve injury associated with humeral shaft fracture should be around 3 months, and the surgical nerve repair should not be performed later than the 6 months after injury. The energy of trauma may be a factor predicting patient’s final recovery following the treatment.